Nightmare disorder and REM sleep behavior disorder in inflammatory arthritis: Possibility beyond neurodegeneration. Issue 3 (15th February 2019) - Baldelli, Luca; Addimanda, Olga; Burattini, Marco; Chiaro, Giacomo; Brusi, Veronica; Pignotti, Elettra; Meliconi, Riccardo; Provini, Federica
Abstract: Objectives: To investigate the prevalence of REM sleep behavior disorder (RBD) in patients with inflammatory arthritis (IA) to ascertain if RBD could be an internal red flag signaling a fluctuating state of inflammation based on the theory of "protoconsciousness". Materials & Methods: One hundred and three patients with a confirmed diagnosis of IA were consecutively recruited. The patients underwent general (IA activity, functional status, laboratory tests) and neurological evaluations. A neurologist investigated RBD and REM sleep parasomnias in a semi‐structured interview. Sleep quality was assessed with the Pittsburgh Sleep Quality Index, while the risk of obstructive sleep apnea syndrome (OSAS) was evaluated with the Berlin questionnaire. Beck Depression Inventory II and State‐Trait Anxiety Inventory investigated depression and anxiety. Results: Patients had a mean age of 53.7 ± 14.6 years, 65% were women; 57.3% were in a clinically active phase of IA. Two women fulfilled ICSD‐3 criteria for RBD appearing 11 years after and 20 years before IA onset respectively. 31 patients scored positive for nightmare disorder (ND), 8 for recurrent isolated sleep paralysis. 65 (63.1%) patients reported poor sleep quality and 25 (24.3%) resulted at high risk for OSAS. 32 (31.0%) patients scored positively for depression or anxiety. Conclusions: The prevalence of RBD in patients with IA did not differ from that in the general population, whereas ND presented a 2‐fold increased prevalence. Whether RBD can be considered a red flag signaling an internal danger remains an open question, while ND may be a new player in this intriguing relation. Abstract : We investigated RBD prevalence in 103 inflammatory arthritis patients, outside a neurological setting considering RBD as a signal of internal danger according to protoconsciousness theory. Prevalence of RBD in inflammatory arthritis did not differ from general population while Nightmare disorder showed a high prevalence. RBD remains related to neurodegeneration while nightmares' role is still an open issue.